2021
DOI: 10.1016/j.physbeh.2021.113557
|View full text |Cite
|
Sign up to set email alerts
|

Strain comparisons in inhibitory discrimination learning and novel object recognition procedures

Abstract: Highlights Behavioural comparisons of albino Wistar and pigmented Lister Hooded rats. Within-subjects inhibitory learning ( A +/AX-) and novel object recognition variants. Wistars showed clearer inhibitory discrimination than Lister Hooded rats. Novel object recognition discriminations showed strain differences in consistency. Wistars are good for associative learning and basic object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This ratio was statistically significantly (p < 0.05) increased by 98.6% after DPG was administered to cadmium-intoxicated rats, reflecting recognition memory improvement. Of note, the obtained values for the discrimination ratio in control rats are in agreement with previously published studies [40][41][42][43][44][45]. In addition to the discrimination ratio, we measured the total exploration time (Figure 2B) and the mean object exploration time (for the old and novel objects; Figure 2C).…”
Section: Dapagliflozin Rescued Recognition Memory Deterioration In Ca...supporting
confidence: 90%
“…This ratio was statistically significantly (p < 0.05) increased by 98.6% after DPG was administered to cadmium-intoxicated rats, reflecting recognition memory improvement. Of note, the obtained values for the discrimination ratio in control rats are in agreement with previously published studies [40][41][42][43][44][45]. In addition to the discrimination ratio, we measured the total exploration time (Figure 2B) and the mean object exploration time (for the old and novel objects; Figure 2C).…”
Section: Dapagliflozin Rescued Recognition Memory Deterioration In Ca...supporting
confidence: 90%
“…Despite the overwhelming similarities in the developmental trajectories of the three rat strains in our study, there are some small differences, with the most usual being in the amount of exploration different strains exhibited in sample or/and test phase. This could reflect known differences in vision between albino and pigmented rat strains ( Andrews et al, 1995 ; Prusky et al, 2002 ; Kumar et al, 2015 ; Waite et al, 2021 ). Despite the differences in object exploration between rat strains, our correlation analyses did not reveal any consistent relationships.…”
Section: Discussionmentioning
confidence: 99%
“…However, Renard et al ( 46) also found that saline-treated LH but not Wistar rats were able to recognize a novel object after a 120 min inter-trial interval. In contrast, a more recent study showed that both Wistar and LH rats performed well in the NOR test even after a 24 h inter-trial interval (49). To fully understand the role of eCB and strain interactions on behavior, more studies using both albino and pigmented strains are needed.…”
Section: Urb Does Not a Ect Recognition Memory In Lister Hooded Ratsmentioning
confidence: 93%